Digital Therapeutics for Cognitive Impairment: Exploring Innovations, Challenges, and Future Prospects - Grace Yuange Zang; Keqin Rao; Jing Wu; Yunhan He; Yi Tang; Leiyu Shi (Journal of Medical Internet Research)
AbstractRecent advancements in cognitive neuroscience and digital technology have significantly accelerated the adoption of digital therapeutics for cognitive impairment. This viewpoint explores the innovative applications of digital therapeutics in the assessment, intervention, management, and monitoring of cognitive disorders while highlighting key challenges that impede their widespread integration into clinical practice. Drawing on the definition of cognitive digital therapeutics (CDTx) and the multistakeholder collaboration required for its development and implementation, this paper examines the role of digital technologies in cognitive health and explores challenges from multiple perspectives, including clinical practice, policy framework, user adoption, ethics and privacy, and data interoperability and system integration. In addition, this viewpoint offers strategic recommendations to address the challenges and future prospects of CDTx, emphasizing the importance of multistakeholder collaboration, prioritizing user-centered design, and leveraging emerging technologies such as artificial intelligence to enhance the scalability, sustainability, and future integration of CDTx.